Antimicrobial use and antimicrobial resistance in Escherichia coli in semi-intensive and free-range poultry farms in Uganda - Mbatidde, Irene; Ndoboli, Dickson; Ayebare, Dreck; Muloi, Dishon; Roesel, Kristina; Ochieng, Linnet; Dione, Michel M.; Tenhagen, B.-A.; Biryomumaisho, S.; Wampande, E.; Wieland, Barbara; Olsen, J.E.; et al. (Elsevier, 2024)
Livestock associated antimicrobial resistance (AMR) can reduce productivity and cause economic losses, threatening the livelihoods of poor farming communities in low-income settings. We investigated the practices and risk factors for increased antibiotic use, and AMR in Escherichia coli including resistance to human critically important antibiotics like cefotaxime and colistin in semi-intensive and free-range poultry farms in Uganda. Samples and farm management data were collected from 402 poultry farms in two districts between October 2021 to March 2022. Samples were processed to isolate E. coli and to quantify cefotaxime (CTX) and colistin (COL) resistant coliforms. The identification of presumptive E. coli isolated on MacConkey agar without antibiotics, was confirmed by matrix-assisted laser desorption/ionization-time of flight mass spectrometry and subjected to antimicrobial susceptibility testing by disk diffusion using EUCAST guidelines. Our models indicated that antibiotic use was associated with production intensity, and type of feed used. Moreover, semi-intensive farmers had better knowledge on antibiotic use compared to farmers in the free-range system. In semi-intensive farms, 52% harbored COLR and 57% CTXR coliforms. In free-range farms, 54% had COLR and 67% CTXR coliforms. Resistance to tetracycline, ampicillin and enrofloxacin were more frequent in semi-intensive farms compared to the free-range farms. Multi-drug resistant E. coli were identified in both poultry production systems despite different management and antibiotic use practices. There was no significant relationship between antibiotic use and resistance for the six antibiotics tested.